Baseline Characteristics of Participants in the ASPREE (ASPirin in Reducing Events in the Elderly) Study - McNeil, John J; Woods, Robyn L; Nelson, Mark R; Murray, Anne M; Reid, Christopher M; Kirpach, Brenda; Storey, Elsdon; Shah, Raj C; Wolfe, Rory S; Tonkin, Andrew M; Newman, Anne B; Williamson, Jeff D; et al. (The journals of gerontology. Series A, Biological sciences and medical sciences, 2017)
There are no primary prevention trials of aspirin with relevant geriatric outcomes in elderly people. ASPirin in Reducing Events in the Elderly (ASPREE) is a placebo-controlled trial of low-dose aspirin that will determine whether 5 years of daily 100-mg enteric-coated aspirin extends disability-free and dementia-free life in a healthy elderly population and whether these benefits outweigh the risks. Set in primary care, this randomized double-blind placebo-controlled trial has a composite primary endpoint of death, incident dementia or persistent physical disability. Participants aged 70+ years (non-minorities) or 65+ years (U.S. minorities) were free of cardiovascular disease, dementia, or physical disability and without a contraindication to, or indication for, aspirin. Baseline data include physical and lifestyle, personal and family medical history, hemoglobin, fasting glucose, creatinine, lipid panel, urinary albumin:creatinine ratio, cognition (3MS, HVLT-R, COWAT, SDMT), mood (CES-D-10), physical function (gait speed, grip strength), Katz activities of daily living and quality of life (SF-12). Recruitment ended in December 2014 with 16,703 Australian and 2,411 U.S. participants, a median age of 74 (range 65-98) years and 56% women. Approximately 55% of the U.S. cohort were from minority groups; 9% of the total cohort. Proportions with hypertension, overweight, and chronic kidney disease were similar to age-matched populations from both countries although lower percentages had diabetes, dyslipidemia, and osteoarthritis. Findings from ASPREE will be generalizable to a healthier older population in both countries and will assess whether the broad benefits of daily low-dose aspirin in prolonging independent life outweigh the risks.